2023
DOI: 10.1037/tra0001244
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the COVID-19 pandemic on rural survivors of intimate partner violence.

Abstract: Objective: Our objective was to understand experiences of intimate partner violence (IPV) by survivors living through the COVID-19 pandemic in a rural area. Method: Structured interviews were conducted with a purposive sample of IPV survivors, 93% of whom identified as women, living in a rural parish (county) in Louisiana (n = 41). Interviews included COVID-19-related stressors (e.g., rent stress due to the pandemic) and posttraumatic stress disorder (PTSD; Primary Care PTSD Screen for DSM-5) and resilience (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The rights and well-being of children and adolescents during the pandemic were explored in two studies (34, 35). Suleman et al (34) found that efforts to control the spread of COVID-19 worsened existing inequities for marginalized children and youth.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The rights and well-being of children and adolescents during the pandemic were explored in two studies (34, 35). Suleman et al (34) found that efforts to control the spread of COVID-19 worsened existing inequities for marginalized children and youth.…”
Section: Resultsmentioning
confidence: 99%
“…Structural inequities, xenophobia, and racism were magnified during the pandemic, further affecting the mental health and development of children and youth. Craig et al (35) found that during the pandemic control measures, there were higher rates of mental health symptoms and substance use among Canadian adolescents, with differential impacts by gender, with over 50% of youth engaging in some form of substance use in the past 90 days and almost 20% engaging in substance use at least once a week. The studies emphasized the need for enhanced investment in services for children and the establishment of mechanisms to uphold their rights (34, 35).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations